The Effectiveness Of Using Card Sort Method In Arabic Language Learning In Improving The Mastery Of Arabic Vocabulary Of Students In Class Vii Smp Islam Al-Ulum Terpadu Medan - Lubis, Isnaini Anggina; Al-Rasyid, Harun (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
Arabic is the second most important foreign language in Indonesia after English. Arabic is generally taught in madrasahs and pesantrens, so its coverage is not as widespread as English, which is taught in almost all schools. Furthermore, Arabic is a key language for understanding Islamic teachings. Therefore, a good mastery of vocabulary is essential for students to communicate fluently and comprehend texts effectively. This study aims to examine the effectiveness of the Card Sort method in improving the Arabic vocabulary mastery of seventh-grade students at SMP Islam Al-Ulum Terpadu Medan on the topic of alwān (colors). The study uses a quantitative method with a quasi-experimental one-group pretest-posttest design. The results show that, first, the Card Sort method is effective in enhancing students’ vocabulary mastery on the material of alwān. Second, the effectiveness of the Card Sort method is evident from the average pretest score of 57.12 and the average posttest score of 85.52, with an n-Gain value of 82.83%, indicating a very good improvement. These findings confirm that the Card Sort method can be an effective approach in Arabic language learning, particularly in improving students’ Arabic vocabulary mastery